Engineering Planning Method and Control Modes for Debris Flow Disasters in Scenic Areas - Gong, Xing-Long; Chen, Xiao-Qing; Chen, Kun-Ting; Zhao, Wan-Yu; Chen, Jian-Gang (Frontiers in Earth Science, 2021)
Compared with debris flows in other areas, debris flows in scenic areas not only seriously threaten residents, tourists, roads, walkways and other infrastructure, but also cause considerable damage to the landscapes and ecosystems of these areas. Extreme rainfall events in the future will increase the complexities and challenges involved in debris flow control in scenic areas. Currently, the systematic planning of the entire scenic area is not considered in the treatment of debris flows. It is not possible to realize the rapid planning of any debris flow gully control project in a scenic area and to quantify the volume of debris flow material held by each engineering structure. Based on field investigations and data collected from debris flow control projects in gullies in Jiuzhaigou Valley in China, an engineering planning method for debris flow control projects in scenic areas is herein proposed. Based on the planning method for debris flow control engineering in scenic areas, the challenges confronting existing control projects in scenic areas are discussed. Moreover, based on the example of Jiuzhaigou Valley, corresponding control engineering schemes for debris flow gullies in Xiajijie Lake Gully, Zhuozhui Gully, Xuan Gully, Pingshitou Gully, and West-Zhuozhui Gully are formulated. Four control patterns for debris flow disasters in scenic areas are proposed, namely, “blocking + deposit stopping”, “deposit stopping”, “blocking”, and “drainage + deposit stopping”, which provide a systematic control strategy for post-earthquake debris flow disaster management in Jiuzhaigou Valley and other similar scenic areas.